Tinjauan Hukum Islam terhadap Pengobatan Menggunakan Autonomous Sensory Meridian Response (ASMR) bagi Penderita Insomnia: Islamic Law Review on Treatment Using Autonomous Sensory Meridian Response (ASMR) for Insomnia Sufferers - Akhmad Hanafi Dain Yunta; Putra Alam; Ismail Al Hafidz Mahmud (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2025)
This study examines the Islamic legal perspective on using Autonomous Sensory Meridian Response (ASMR) as therapy for insomnia, a condition that disrupts worship quality and daily functioning. The research problem focuses on whether ASMR, as a modern therapeutic method, complies with Islamic law, given its potential triggers involving audio, touch, and visual elements. The objective is to analyze ASMR's psychological and neurological effects on insomnia and assess its permissibility under Islamic principles. Using a normative-conceptual approach through library research, the study draws on Quranic verses, Hadith, and empirical evidence. Findings indicate ASMR's efficacy in improving sleep via alpha-wave stimulation and neurohormonal mechanisms (e.g., oxytocin release). Jurisprudentially, ASMR is deemed mubah (permissible) if it avoids haram elements (e.g., music, aurat exposure) and adheres to ethical boundaries. The study concludes that ASMR is a sharia-compliant complementary therapy for insomnia, contributing to contemporary Islamic jurisprudence by integrating modern therapeutic methods within an ethical framework. Practical implications include guidelines for halal health practices.